Pengaruh Disiplin Kerja Dan Pengembangan SDM Terhadap Kinerja Pegawai Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Tasikmalaya - Lisan Hidayat; Kusuma Agdhi Rahwana; Arga Sutrisna (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the effect of work discipline and human resource development on the performance of the Tasikmalaya Regency Population and Civil Registration Service Employees. This study uses a descriptive method with a quantitative approach. The research population was part of the Tasikmalaya Regency Population and Civil Registration Office employees and used a saturated sampling technique, where all members of the population were sampled, namely 40 respondents. Data collection techniques using interviews and questionnaires. The method used is multiple linear regression analysis with SPSS version 25. The results of this study indicate that Work Discipline (X1) and HR Development (X2) simultaneously have a significant effect on the dependent variable, namely Employee Performance (Y). Work Discipline (X1) partially significant effect on Employee Performance (Y). HR development (X2) partially significant effect on employee performance (Y).